Optimization of RBD Palm Stearin Cargo Handling to Ensure the Smooth Unloading Process on MT Celeste I - Tandililing, Welly; Alamsyah, Nur; Rusman, Rusman (Universitas Hang Tuah, 2026)
RBD Palm Stearin is the solid fraction of palm oil with a high melting point, making it highly sensitive to temperature variations during sea transportation and cargo discharge. This characteristic causes the cargo to solidify easily, especially when vessels operate in low ambient temperatures. On board MT Celeste I, such conditions have led to flow obstructions, cargo pump stoppages, and delays in loading and unloading, adversely affecting operational efficiency a nd work safety.This study aims to analyze the technical, operational, and human factors contributing to cargo solidification and to formulate optimization strategies to ensure safe and efficient discharge operations. A qualitative approach was applied through direct onboard observations, in-depth interviews with crew members and port personnel, and a review of operational documents from December 2023 to December 2024. The data were thematically analyzed to identify causal patterns, event mechanisms, and best practices in temperature control and cargo handling. The research focuses on temperature management, equipment readiness, and strict adherence to Standard Operating Procedures (SOPs) from pre-discharge to final stripping. The results indicate that smooth operations depend heavily on maintaining temperatures above the melting point through well-functioning heaters, effective steam tracing systems, gradual preheating, and even heat circulation. Key challenges include heater leakages, solid accumulation in pipelines or manifolds, thermal effects from ballast operations, and procedural errors. The study recommends implementing real-time temperature monitoring, conducting regular preventive maintenance, enhancing crew competence through technical training, and strengthening SOPs to ensure that heating and cargo discharge processes are carried out safely and efficiently.